2017
DOI: 10.3390/beverages3020020
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameters Affecting the Synthesis of Natural Flavors by Shiitake (Lentinula edodes) during the Production of a Non-Alcoholic Beverage

Abstract: A novel alcohol-free beverage with a fruity, slightly sour, sweetish, fresh, and plum-like flavor was produced by incorporating the edible mushroom shiitake (Lentinula edodes) into the fermentation process. Shiitake pellets were used as a biocatalyst to promote the synthesis of the fruity esters methyl 2-methylbutanoate and 2-phenylethanol from amino acids and an organic acid present in the wort. We investigated the impact of two critical process parameters (volumetric power input and inoculum concentration) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…En el caso de L. edodes, los estudios van dirigidos principalmente al aumento del rendimiento del micelio producido como en los trabajos de (199,(216)(217)(218) ó en el caso del trabajo de (200), donde además de aumentar la biomasa se buscaba aumentar la producción de exopolisacáridos. Igualmente, sobre la producción biotecnológica de esta seta, algunos estudios han buscado determinar las condiciones para la producción de metabolitos como es el caso de los β-glucanos (26), metabolitos de interés clínico y alimentario (296)(297)(298) o para la producción de enzimas con potencial aplicación industrial (299,300).…”
Section: Introductionunclassified
“…En el caso de L. edodes, los estudios van dirigidos principalmente al aumento del rendimiento del micelio producido como en los trabajos de (199,(216)(217)(218) ó en el caso del trabajo de (200), donde además de aumentar la biomasa se buscaba aumentar la producción de exopolisacáridos. Igualmente, sobre la producción biotecnológica de esta seta, algunos estudios han buscado determinar las condiciones para la producción de metabolitos como es el caso de los β-glucanos (26), metabolitos de interés clínico y alimentario (296)(297)(298) o para la producción de enzimas con potencial aplicación industrial (299,300).…”
Section: Introductionunclassified
“…It is known that basidiomycetes can also form 2-phenylethanol (22) de novo or by biotransformation from asparagine or L-phenylalanine, although this occurs in much lower concentrations than yeasts, for example [18,45]. Özdemir et al showed the production of 2-phenylethanol by Lentinula edodes in wort with an OAV of 1.3 [46]. However, based on the peak area change over time, the contribution to the overall aroma of 2-phenylethanol ( 22) might be attributed to its occurrence in the CP-M.…”
Section: Dynamic Changes Of Aroma Compound Formation During Cultivationmentioning
confidence: 99%
“…Los experimentos llevados a cabo en el biorreactor siguieron un diseño factorial con dos factores (flujo de aire y velocidad de agitación) en dos niveles para cada uno, con el objetivo de determinar las condiciones más adecuadas tanto para el crecimiento del hongo como para favorecer la biosíntesis de metabolitos de interés. Después de evaluar diferentes fuentes bibliográficas (Agudelo-Escobar et al, 2017;Domingos et al, 2017;Enman et al, 2008;Özdemir et al, 2017), se ajustaron los rangos de las variables de estudio de la siguiente manera: flujo de aire entre 0.5 vvm a 1.0 vvm y velocidad de agitación entre 80 rpm y 200 rpm, con lo cual se definieron seis experimentos elaborando un diseño central compuesto, tal como se puede apreciar en la tabla 1.…”
Section: Diseño Experimentalunclassified